Problematika Talak Suami Kepada Istri Di Luar Pengadilan (Studi Kasus Talak Di Kecamatan Babalan) - Nikman Nashirin (Journal Smart Law, 2023)
Divorce is the release of bonds, both of which look like the marriage bond which is the relationship that exists between husband and wife. Divorce is defined in terms that talak is eliminating marriage or reducing its halalness with special words. The problem that occurs is that there is a difference in the Fatwa of the Indonesian Ulema Council that the divorce handed down by a husband against his wife outside the Religious Courts is legally valid, whereas according to the Compilation of Islamic Law and also the law reveals that a divorce is considered to occur along with the reasons were since after the Religious Court was unable to reconcile the two parties. This problem raises questions regarding the law of divorce from husband to wife outside the Court according to the Fatwa of the MUI of North Sumatra Province Number 4 of 2011, then how is the law of divorce from husband to wife outside the Court according to KHI, and what are the legal consequences of divorce outside the Religious Court. From these questions, research needs to be done to answer them. The research was conducted by collecting primary data in the form of Fatwa MUI of North Sumatra Province Number 4 of 2011 and KHI, as well as secondary data taken from books, theses, journals and websites related to this research. As a result, according to the Fatwa of the North Sumatran MUI, divorce outside the court is legal and must submit an isbat divorce to the Religious Court so that the divorce is registered. Meanwhile, from the KHI side, with the regulation regarding divorce only falling in the Court, there should be no more conflict regarding the non-falling of divorce outside the Religious Court session.